EMG mapping of the quadriceps in patellofemoral pain syndrome during functional activities: a pilot study. Issue 15 (10th November 2011) - Balachandar, V; Twycross-Lewis, R; Morrissey, D; Barton, C J; Woledge, R C
Abstract : Patellofemoral pain syndrome (PFPS) arises from patellofemoral articulation, caused in part by inefficient quadriceps muscle activity. Many studies have used surface electromyography (sEMG) to investigate quadriceps activity, with conflicting results. This study is novel in the use of 64-channel surface EMG combined with motion capture. The aim was to create three-dimensional (3-D) EMG maps based on quadriceps muscle amplitude, muscle onset, and lower-limb kinematics in participants with and without patellofemoral pain (PFP) during functional activity using a 2×2 factorial design. Two participants with PFP and three asymptomatic controls were recruited. 64-channel EMG onset and amplitude from the vastus lateralis (VL), rectus femoris (RF), and vastus medialis oblique (VMO) muscles, and motion-analysis data were collected simultaneously during functional activity. Correlation coefficients (CCs) were calculated for within subject and between subject groups. CCs identified significant patterns of activity within subject groups (P<0.01), and more varied patterns in the PFP group. Visual analysis identified that vastii muscle activity was higher in PFP participants than controls for a given movement. Evidence suggests that patterns of activity are more variable in PFP participants. Variability in quadriceps muscle activity may result in erratic patella-kinematics, lateral directed tension, and an increased load on the lateral patella facet resulting in PFP. There is currently a paucity of research investigating patterns of quadriceps muscle activity in PFPS, which needs to be addressed considering its role in the theoretic rational for PFPS. There is substantial scope for further research, and findings may lead to an application towards screening, rehabilitation, and diagnosis. EMG patterns of activity within subject groups are consistent during functional movement. Patterns of activity are more variable, and VMO contraction appears less efficient in PFP participants than in asymptomatic controls